(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Purpose: The medical devices are used in the diagnosis, treatment, prostheses, resuscitation, and monitoring of the patients. These range from relatively simple external objects to high-tech internal devices. These can guide pathologists towards the cause of death by indicating the organ system they belong to, when present in situ at as breast implants; surgical devices such as sutures, slips, adhesive and mesh; neurological devices such as vetriculo-peritoneal shunts; neonatal devices such as umbilical cord clip; and orthopedic devices such as plasters, external/internal fixators, braces and slings. Conclusion - Device and procedural-related deaths do occur but as exception rather than a rule. Improper use or implantation, underlying natural disease, tissue reaction resulting in dislodgement or ineffective functioning of the device are more common situations. In our study, all the medical devices were instituted in the body to manage the pathological process or abnormal physiology. The failure of the devices occurred in its natural course and did not cause any additional complications.